Formulasi dan Uji Mutu Fisik Sediaan Body Lotion Ekstrak Daun Alpukat (Persea americana Mill) dengan Variasi Konsentrasi Trietanolamin dan Asam Stearat Sebagai Emulgator - Lestari, Salsa Bila; Waris, Muhammad Anugerah Alam; Setyani, Indrawati Kurnia (NUTRITURE JOURNAL; Vol 3 No 3 (2024): Nutriture Journal, 2024)
Background: Body lotion is one type of cosmetics that has a formulation containing a homogeneous oil phase and water phase so as to provide moisture to the skin, and can be applied easily. One of the natural ingredients that can be formulated into body lotion preparations and is useful for fighting and protecting the skin from free radicals is avocado leaves. Objective: This study aims to determine the effect of variations in the concentration of triethanolamine and stearic acid as emulgators on the physical quality characteristics of avocado leaf extract (Persea americana Mill) body lotion preparations. Method: The method in this study uses experimental methods . Results: This study tested several physical quality parameters, namely organoleptical tests with the results of lotions that are brown in color, have a distinctive aroma of avocado leaf extract, with a soft texture and semi-solid shape. Homogeneity test results there are results that are not homogeneous in formula 1. The pH test results obtained average results of 7.87, 7.05, and 5.9. The adhesion test results obtained results with an average of 4.64 seconds, 5.55 seconds, and 6.37 seconds. The viscosity test results obtained average results of 2495 cps, 3874 cps, and 5539 cps. The results of the spreadability test obtained an average of 6.91 cm, 6.63 cm, and 6.17 cm, and the results of the irritation test in this study did not find results that irritated the panelists' culottes, which means that the lotion is safe for daily use. Conclusion: Based on the results of the research that has been obtained from the results of the physical quality test of avocado leaf extract body lotion preparations with varying concentrations of triethanolamine and stearic acid, it can be concluded that the results of the physical quality test with varying concentrations of triethanolamine and stearic acid have a significant effect on the pH test, adhesion test, spreadability test, and viscosity test.